Respuesta :

6x - 6y = 42
7x + 6y = -68
------------------add
13x = - 26
x = -26/13
x = -2

6x - 6y = 42
6(-2) - 6y = 42
-12 - 6y = 42
-6y = 42 + 12
-6y = 54
y = -54/6
y = -9

solution is : (-2,-9)
Hello there!

6x - 6y = 42
7x + 6y = -68

We can solve this equation by using the elimination or substitution form.

--------------------------------------------------------------
We gonna solve 6x - 6y = 42 for x
6x = 42 + 6y
x = (42+6y)/6
x = y + 7

Now we need to substitute 7 + y for x in 7x + 6y = -68
That means, everywhere we find x, we will replace it by y+7
7( y + 7) + 6y = -68
7y + 49 + 6y = -68
13y + 49 = -68
13y = -68 - 49
13y = -117
y = -117/13
y = -9

Since we find the value of y which is -9, it is easier for us to find x. All we have to do is to replace -9 everywhere we find y

Let's start by substitute -9 for y in x= y+7
x = y + 7
x = -9+7
x= -2

Final answer: x= -2, y=-9 >> (-2;-9)

I hope my answer helps you tonight!